Effect of minocycline in COVID-19 patients: A randomized clinical trial - Danial Esmaeilzadeh; Mohammad Shariati Rad; Mehrdad Esmaeilzadeh; Bibi Marjan Razavi; Amirhooshang Mohamadpoor; Hossein Hosseinzadeh (Journal of Research in Clinical Medicine)
Introduction: Minocycline a semi-synthetic tetracycline is a potential therapeutic option for COVID-19 because of its anti-inflammatory and immunomodulatory effects. Moreover, its antioxidant, antiviral, and antiapoptotic effects have been proven. In this study, the efficacy of minocycline in the therapy of COVID-19 patients has been evaluated. Methods: A randomized double-blind placebo-controlled clinical trial was performed in Mashhad, Iran. 40 outpatients were randomized to either the treatment with the minocycline group or the placebo group, in a 1:1 ratio with 20 patients in each group. The Iranian National COVID-19 Therapy Regimen at the time was used in both groups and patients in the treatment group also received oral minocycline 100 mg twice day for 14 days. Patients in both groups were followed on days 3, 7, and 14 after initiating therapy for clinical symptom improvement, improvement of lymphocytes, leukocytes, C-reactive protein (CRP) and SpO2. Results: A total of 40 patients with similar demographic and disease characteristics were enrolled. Results showed that the time interval until clinical symptoms improvement was significantly reduced in the minocycline group (6.85±0.79, day) compared to the placebo (10.95±1.18, day) group (P=0.006). Moreover, the time interval until leukocytes reaching normal limits was significantly reduced in the minocycline group (3.95±0.59, day) compared to the placebo (6.72±1.25, day) group (P=0.046). Conclusion: In this randomized double-blind placebo-controlled study, minocycline (100 mg, BID for 14 days) reduced the duration of clinical symptoms improvement as well as the duration of white blood cell (WBC) normalizing in outpatients of COVID-19 disease.